Influence of different processing times on the quality of Polygoni Multiflora Radix by metabolomics based on ultra high performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry. Issue 9 (19th April 2017) - Yu, Xie‐an; Ge, Ai‐hua; Zhang, Lu; Li, Jin; An, Mingrui; Cao, Jun; He, Jun; Gao, Xiu‐mei; Chang, Yan‐xu
Abstract : A metabolomics method based on ultra high performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry was developed to evaluate the influence of processing times on the quality of raw and processed Polygoni Multiflora Radix . Principal component analysis and partial least‐squares discriminant analysis was used to screen the potential maker metabolites that were contributed to the quality changes. Then these marker metabolites were selected as variables in Fisher's discriminant analysis to establish the models that were used to distinguish the raw and processed Polygoni Multiflora Radix in the markets. Additionally, 36 compounds were identified. Twelve raw Polygoni Multiflora Radix samples and 23 processed Polygoni Multiflora Radix samples were distinguished. The results showed that the 12 raw Polygoni Multiflora Radix samples belonged to the group of processing time of 0 h, and two processed Polygoni Multiflora Radix samples were part of the group of processing times of 4 h, 12 samples belonged to group of processing times of 8 to 16 h, and nine samples were the group of processing times of 24 to 48 h. The results demonstrated that the method could provide scientific support for the processing standardization of Polygoni Multiflora Radix .